Jihad Dalam Perspektif Sejarah Pemikiran Islam - Muh Muhsin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to examine the concept of jihad in various historical periods of Islamic thought and how its meaning has developed in line with the social and political context of Muslims. The method used is qualitative with a historical-analytical approach, through a literature review of classical and modern sources that discuss jihad. The results show that jihad is not always synonymous with warfare (qital), but has spiritual, social, and intellectual dimensions. In the history of Islamic thought, the concept of jihad has been reinterpreted, from physical struggle against the enemy to efforts to improve oneself and society. This broader interpretation of jihad reflects the dynamic needs of the ummah in various situations. Therefore, the understanding of jihad must be contextual, focusing not only on the military aspect, but also on the contribution to the progress of the ummah and humanity as a whole.